1983
DOI: 10.1149/1.2119517
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Conducting Polythiophene and Derivatives

Abstract: Many organic conducting polymers such as polyacetylene, PA (1) ; polyparaphenylene, PPP (2) ; polyparaphenylenesulfide, PPS (2); and polypyrrole, PP (3) have been proposed in the literature. These polymers show reversibility of the doping-undoping process, making them of interest in energy storage. One of the key problems, however, is the poor stability of most of these polymers. Polyacetylene, PA, must be prepared and stored under a rigorously O2 free atmosphere and at a low temperature (4). Polypyrrole, PP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(85 citation statements)
references
References 5 publications
5
79
0
1
Order By: Relevance
“…[38][39][40] It is important to note that the conductivities obtained by doping with FeCl 3 can also be limited by the oxidation potential of the polymers. However, it is more interesting to use a medium strength dopant such as ferric chloride or ferric tosylate, compared to nitrosonium salts (NOBF 4 or NOBF 6 ) where overoxidation and degradation often becomes a problem.…”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40] It is important to note that the conductivities obtained by doping with FeCl 3 can also be limited by the oxidation potential of the polymers. However, it is more interesting to use a medium strength dopant such as ferric chloride or ferric tosylate, compared to nitrosonium salts (NOBF 4 or NOBF 6 ) where overoxidation and degradation often becomes a problem.…”
Section: Resultsmentioning
confidence: 99%
“…Although recent research has shown that the emeraldine salt of PANI (EPANI) can be successfully fabricated in a biocompatible form [73,74], modern biomedical CPs are typically composed of heterocyclic aromatics, such as derivatives of thiophene and pyrrole [75][76][77][78]. Specifically, poly(3,4-ethylenedioxythiophene) (PEDOT) and polypyrrole (PPy) have been widely studied for their superior environmental and electrochemical stability [79][80][81][82]. Figure 2 shows the chemical structure of various thiophene derivatives including EDOT, EDOT-MeOH and 3-alkylthiophene.…”
Section: Conventional Cp Fabricationmentioning
confidence: 99%
“…Platinum electrodes were used because of their inert behavior against monomers and polymers. In addition, polymers generated on platinum electrodes show in general higher conductivities than films generated on any other electrodes [15,17,113,114]. penetrate into the film due to its smaller size [65].…”
Section: Theoretical Calculation Methodsmentioning
confidence: 99%
“…Since the first reports of the oxidation of pyrrole, many other aromatic systems have been found to undergo electropolymerization to produce conducting polymers, like thiophene [14][15][16][17], furan [14], selenophene [18], aniline [19][20][21][22], azulene [23,24], indole [14], Paraphenylene [25,26], as well as many substituted, multi-ring and polynuclear aromatic hydrocarbon systems (Table 1). It was found that all of the resulting polymers have a conjugated backbone, which is required for conductivity.…”
Section: Polyheterocycles As Conducting Polymersmentioning
confidence: 99%